Mecanismo de planificación y diseño urbano paisajístico sustentable aplicado a la recuperación y readecuación del espacio público. Caso de estudio Parque La Pradera - Gordillo Granda, Maritza Maribel (2015)
In the present investigation we worked on a mechanism for planning and sustainable landscape urban design for the recovery and upgrading of public space, taking as a case study and application to Parque La Pradera, through analysis and research it was determined a mechanism based on indicators , the same principles and criteria that are based on the 3 factors of sustainable landscape (social, economic and environmental), socially were strengthened community ties through community participation by the residents of Barrio La Pradera, who with their collaboration and participation park design was achieved, the same that is based on the needs of the residents. During the design process we worked with the concept of landscape and sustainability the same which is based on knowledge and potential of nature and environmental complexity in order to raise awareness among residents about the damage that is done the ecosystem and how you can make a difference.